Titanic - Cameron, James; Landou, Jon; Twentieth Century Fox; Paramount Pictures; Lightstorm Entertainment (Baverley Hills, CA : Twentieth Century Fox ; Paramount Pictures, 2005)
The story of a passionate romance aboard the doomed ocean liner Titanic, framed by an account of a present-day salvager's efforts to investigate the ruins of the ship
Title from title screen
Originally produced as a motion picture in 1997
Director of photography, Russell Carpenter ; edited by Conrad Buff, James Cameron, Richard A. Harris ; music composed by James Horner
Casts: Leonardo DiCaprio, Kate Winslet, Billy Zane, Kathy Bates, Frances Fisher, Gloria Stuart, Bernard Hill, Jonathan Hyde, Victor Garber, David Warner, Danny Nucci, Suzy Amis, Bernard Fox, Bill Paxton.
With Chinese and Malay subtitles
Keywords: Titanic (Steamship) -- Drama; Shipwrecks -- North Atlantic Ocean -- Drama; Feature films; Love in motion pictures